2003
DOI: 10.1038/sj.bjc.6601257
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α increases human melanoma cell invasion and migration in vitro: the role of proteolytic enzymes

Abstract: Inflammatory mediators have been reported to promote malignant cell growth, invasion and metastatic potential. More specifically, we have recently reported that tumour necrosis factor alpha (TNF-a) increases melanoma cell attachment to extracellular matrix (ECM) substrates and invasion through fibronectin. In this study, we extend these investigations asking specifically whether the TNF-a effect on cell invasion and migration involves activation of proteolytic enzymes. We examined the effect of TNF-a on melano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
54
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 26 publications
6
54
0
2
Order By: Relevance
“…We also found TNF-a to cause a modest increase in proteolytic activity, which could be blocked effectively using a 2 macroglobulin (Katerinaki et al, 2003), but with no concomitant increase in matrix metalloproteinase 2 or 9 activation or expression. However, the above studies did not consider whether melanoma invasion through fibronectin was attributable specifically to an increase in cell migration or to an increase in invasion.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…We also found TNF-a to cause a modest increase in proteolytic activity, which could be blocked effectively using a 2 macroglobulin (Katerinaki et al, 2003), but with no concomitant increase in matrix metalloproteinase 2 or 9 activation or expression. However, the above studies did not consider whether melanoma invasion through fibronectin was attributable specifically to an increase in cell migration or to an increase in invasion.…”
mentioning
confidence: 61%
“…In vitro and in vivo invasion may involve both increased migration and increased proteolytic breakdown of the matrix. Thus, we recently found that while TNF-a did not cause an obvious upregulation of proteolytic activity in HBL cells, the introduction of a broadspectrum protease inhibitor (a 2 macroglobulin) was able to block TNF-a-stimulated cell invasion and cell migration (Katerinaki et al, 2003). In the current study, we compared two methods for measuring cell migration, both based on introducing a 'scratch' to a cultured monolayer of cells (adapted from a method previously reported for keratinocytes (Cha et al, 1996)).…”
Section: Discussionmentioning
confidence: 99%
“…IFNÁ may also promote metastatic diffusion of melanoma cells through a down regulation of the processing of tumor antigens (20)(21)(22). TNF· promoted the invasiveness of human melanoma cells through the stimulation of the expression of integrin receptors (23), or cell-bound degradative enzymes (24).…”
Section: Introductionmentioning
confidence: 99%
“…Reports have proved that TNF-a enhances metastatic properties in many cancer cell lines. [34][35][36][37] The in vitro TNF-a stimulation model we have recently developed provides a new way to characterize the importance of signaling molecules in cancer cells for cytokine-induced metastasis. Several signaling pathways related to enhanced metastasis have been studied; however, the contribution of TAK1 to tumor metastasis has never been investigated.…”
mentioning
confidence: 99%